Manajemen Proyek Sistem Informasi Pada Sistem Pengelolaan Data Reseller PT. Replay - Kurniadi, Erik; Rahmah, Syifa; Suseno, Endra; Nugraha, Dadan (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2024)
Project management is a strategy that needs to be carried out to achieve efficiency and effectiveness in a company. Project management framework as a measuring tool for managing work schedules. PT Replay is a branch of the PT Teknohost company that operates in the technology services sector where the obstacle currently faced is that it does not have a reseller data management and billing information system. Apart from that, the data collection and billing carried out at the company are still manual, namely using Microsoft Excel, so an information system is needed to overcome this. This research aims to manage the information system development project at PT Replay, which is prepared using the Work Breakdown Structure (WBS) with the waterfall system development method in planning. Therefore, a web-based reseller data management information system was built at PT Replay to make it easier to manage reseller data.